Dimensi yang Terkandung dalam Pendidikan Islam Multikultural - Teri Andrian; Aripin (CV Putra Publisher, 2023)
Multiculturalism is very important because it is driven by the desire to increase human harmony and spread peace throughout society. In Indonesian multicultural education, the teachings of peace and conflict resolution are based on Islam with Rasulullah SAW as Rahmatan lil'Alamin. This attitude of mutual tolerance will produce dynamic cultural diversity and richness of national identity which must be preserved. In fact, diversity serves as a bonding tool. a body of explanations that recognizes and values ​​the importance of cultural and ethnic diversity to the lives of individuals, groups and nations, as well as to social experiences, personal identities and educational opportunities. Equal/fair education or only pedagogy, knowledge construction, reduction of prejudice, content integration, school culture empowerment components, social structure, and empowerment components are all components of multicultural education. Religious teachings about the growth of multicultural ideas are also taught in multicultural Islamic education.